2004
DOI: 10.1016/s1059-1311(03)00082-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antiepileptic drugs on visual performance

Abstract: Visual disturbances are a common side-effect of many antiepileptic drugs. Non-specific retino- and neurotoxic visual abnormalities, that are often reported with over-dosage and prolonged AED use, include diplopia, blurred vision and nystagmus. Some anticonvulsants are associated with specific visual problems that may be related to the mechanistic properties of the drug, and occur even when the drugs are administered within the recommended daily dose. Vigabatrin, a GABA-transaminase inhibitor, has been associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 125 publications
4
65
1
Order By: Relevance
“…1,2 Another antiepileptic drug that increases cerebral GABA-levels is vigabatrin (inhibits GABA-transaminase), which has been shown to cause severe, persistent visual field constriction. [3][4][5][6] Several electrophysiological studies of patients treated with vigabatrin, have demonstrated reduced photopic amplitudes indicating actual dysfunction of an unspecified cell level in the retina.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Another antiepileptic drug that increases cerebral GABA-levels is vigabatrin (inhibits GABA-transaminase), which has been shown to cause severe, persistent visual field constriction. [3][4][5][6] Several electrophysiological studies of patients treated with vigabatrin, have demonstrated reduced photopic amplitudes indicating actual dysfunction of an unspecified cell level in the retina.…”
Section: Introductionmentioning
confidence: 99%
“…In patients of one year carbamazepine treatment, central and paracentral colour vision function decrease transparently.87 However, as this case was not identified in some human studies, this effect is not accepted by everyone. 72 In a cross-sectional study done on 18 patients being treated by valproate monotherapy for two-twenty years, colour vision defect was only seen on 2 patients at minor level. 88 Cones sensitive to short wavelength are thought to be effected by antiepileptic drugs.…”
Section: Antiepilepticsmentioning
confidence: 99%
“…[72][73][74] In the year of 2001, Young et. al 75 have shown that clonazepam is 100% effective in treatment of 5 patients with idiopathic downbeat nystagmus.…”
Section: Benzodiazepinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Topiramate has also been associated with an increased risk of renal calculus formation and with cases of closed-angle glaucoma. 23 Topiramate has up to 95 per cent bioavailability and is, in the absence of an enzyme inducer, largely renally excreted in an unchanged form. It is potentially susceptible to large reductions in plasma concentration (up to 50 per cent) when co-administered with an enzyme-inducing drug.…”
Section: Topiramatementioning
confidence: 99%